Konflik Palestina: Jihad Netizen Indonesia, Solidaritas Atau Pelanggaran Hukum - Andi Satria; Rifqah Rahmayani Tanjung; Raihan Ismail Sirait; Josua Joswinto Sihotang (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
Islam is a religion that brings a message of peace not only to Muslims but even to nonMuslims, so it is no wonder that Allah calls it the religion of rahmatan lil alamin. However, several groups and factions consider Islam to be an extreme religion, causing chaos, commotion and war by using the word jihad. The existence of a war between Islam and the infidels at the time of the Prophet and his companions occurred purely because it was initiated by the opposing side, either because they attacked first or because of betrayal by the infidels. What is happening in India, Miyanmar, Surya, especially what is happening in the State of Palestine today. The attack carried out by Israel, quite a few other Islamic countries were angry and furious about this action which seemed to not consider that human life was not valuable at all. In Indonesia, too, but there is nothing that can be done apart from praying and providing assistance in terms of clothing, food and shelter to meet the needs of our brothers and sisters in Palestine and it is not uncommon for Muslims in Indonesia to go to Palestine with the aim of fighting to uphold the banner of Islam in an effort to reclaim Palestinian land.